Virulence Properties of Shiga Toxin-Producing Escherichia coli (STEC) Strains of Serogroup O118, a Major Group of STEC Pathogens in Calves - Wieler, L. H. (American Society for Microbiology, 1998)
Shiga toxin-producing Escherichia coli (STEC) strains of serogroup O118 are the most prevalent group among STEC strains in diarrheic calves in Germany (L. H. Wieler, Ph.D. thesis, University of Giessen, 1997). To define their virulence properties, 42 O118 (O118:H16 [n = 38] and O118:H− [n = 4]) strains were characterized. The strains displayed three different Stx combinations (Stx1 [36 of 42], Stx1 and Stx2 [2 of 42], and Stx2 [4 of 42]). A total of 41 strains (97.6%) harbored a large virulence-associated plasmid containing hly(EHEC) (hly from enterohemorrhagic E. coli). The strains’ adhesive properties varied in relation to the eukaryotic cells tested. Only 28 of 42 strains (66.7%) showed localized adhesion (LA) in the human HEp-2 cell line. In contrast, in bovine fetal calf lung (FCL) cells, the number of LA-positive strains was much higher (37 of 42 [88.1%]). The locus of enterocyte effacement (LEE) was detected in 41 strains (97.6%). However, not all LEE-positive strains reacted positively in the fluorescence actin-staining (FAS) test, which indicated the attaching and effacing (AE) lesion. In HEp-2 cells, only 22 strains (52.4%) were FAS positive, while in FCL cells, the number of FAS-positive strains was significantly higher (38 of 42 [90.5%; P < 0.001]). In conclusion, the vast majority of the O118 STEC strains from calves (41 of 42 [97.6%]) have a high virulence potential (stx, hly(EHEC), and LEE). This virulence potential and the high prevalence of STEC O118 strains in calves suggest that these strains could be a major health threat for humans in the future. In addition, the poor association between results of the geno- and phenotypical tests to screen for the AE ability of STEC strains calls the diagnostic value of the FAS test into question.